Is practice good enough? Retrieval benefits students with ADHD but does not compensate for poor encoding in unmedicated students - Meredith E. Minear; Jennifer H. Coane; Leah H. Cooney; Sarah C. Boland; Judah W. Serrano (Frontiers in Psychology, 2023)
IntroductionA significant proportion of currently enrolled college students receive support for attention deficit/hyperactivity disorder (ADHD) and these students are often at risk of academic failure. Retrieval practice or self-testing is an effective, accessible, and affordable tool for improving academic performance. Three recent studies found conflicting results with regards to the effectiveness of retrieval practice in this population.MethodsThe present study compared 36 individuals with ADHD to 36 controls. Participants studied Swahili-English word pairs that varied in difficulty. Half of the pairs were repeatedly studied, and the other half repeatedly tested.ResultsOn a final test, all participants showed a benefit of retrieval practice relative to restudy and participant status did not moderate the effect. However, unmedicated individuals with ADHD performed worse overall, both during the encoding phase and on the final test, whereas medicated participants were not significantly different from controls.DiscussionAn examination of self-reported encoding strategies found unmedicated participants used fewer deep strategies at encoding, consistent with prior work on ADHD and memory. Although retrieval practice is effective in this group, improved strategy use may be necessary to ensure performance that is fully equivalent to that of students without ADHD.